Study on the Dynamics of Feed Intake in Suckling Calves - Andreea Ștefania Anton; Radu Ionel Neamț; Daniela Elena Ilie; Alexandru Eugeniu Mizeranschi; Ciprian Valentin Mihali; Ludovic Toma Cziszter (Scientific Papers Animal Science and Biotechnologies)
The aim of this study was to investigate the voluntary concentrates intake in relationship with age, as well as the growth rate of calves. Twenty-one calves divided into three groups were used. The body weight at birth and at weaning, total feed consumption and time that calves stayed in the study were measured. Groups 1, 2 and 3 stayed in the study 17, 29 and 50 days, respectively. Daily concentrate consumption (kg) was determined by weighing the concentrates fed, as well as the leftovers. Total feed and milk consumption per calf per day was 5 kg and 0 L, 5.57 kg and 3.31 L, and 9.57 kg and 5.16 L for groups 1, 2, and 3, respectively. Total weight gain was 13 kg, 22 kg, and 43 kg for groups 1, 2, and 3, respectively. In conclusion, the growth rate is dependent on the age, feed consumption and the number of days of receiving concentrates.